Use of local anesthesia in children: literature review: Penggunaan bahan anastesi lokal pada anak: kajian pustaka - Nurhayani Putri; Leny Sang Surya (Makassar Dental Journal PDGI Makassar, 2021)
Local anesthetic agents are drugs used to relieve pain that may occur during dental procedures, one of them is tooth extraction. Lo-cal anesthetics are divided into two groups, namely esters and amides. Local anesthetics aim to immobilize the sensory nerves locally by administering drugs or other medical interventions so that the patient cannot feel pain for a certain duration of time. The use of local anesthesia is usually combined with topical anesthesia to relieve pain due to needle injection. Giving local anes-thesia to children is a psychological barrier for children because usually children are not tolerant of pain and fear. Providing good dental care without pain and comfort is the dentist's responsibility.